The Online Social Support of Chinese Fellow Townsman in Post Pandemic - Ning Gao (Universitas Muhammdiyah Yogyakarta, 2021)
As a kind of disease risk, the global spread of the COVID-19 may just be a microcosm of the global risk society. Affected by the epidemic, people adopt more online virtual connections and have become more dependent on social media. This paper conducted the online social support of Chinese fellow-townsman analysis via conducting online participatory observations on the QQ group of Xinhua immigrants and conducting in-depth interviews with 15 of them. This study found that the social support obtained by the Chinese Fellow Townsman through the Internet interpersonal mutual aid network has made up for the shortcomings of formal social support to a certain extent. In the risk society, it helps individuals get immediate and personalized help. In terms of online social support sources, the Internet social support of Chinese Fellow Townsman mainly comes from bridging social capital. From the perspective of online support content, the online social support of this group is mainly manifested in emotional support, companionship support, and informational support, and the role of tangible support is relatively weak. As to the support effect, through the Online social support from the group, the peers can obtain timely, diverse, and non-redundant information to help them make better decisions. But the ability of interpersonal networks to provide resources is limited. When necessary, we still need social support from the government and other formal organizations.